ASSESSMENT AND IMPLEMENTATION METHODS OF THE EFFECTIVENESS OF MARKETING ACTIVITIES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article describes the methods of evaluating the effectiveness of marketing activities, the theoretical issues of determining and evaluating the effectiveness of marketing are unique, and the approaches to it are different. Definitions of the economic efficiency of marketing activities using both qualitative and quantitative indicators in the determination and evaluation of marketing efficiency, several methods of determining the economic efficiency of promotional activities are proposed, and the types of marketing control in increasing efficiency are practically based. they were given brief scientific information. The article also reflects the relationship between the main goals of marketing and the main goals of the company.